Fragility Analysis and Risk Assessment of Precast Concrete Frames with "Dry" Connections: A Comparative Study. Issue 3 (November 2021) - Wu, Chenhao
Abstract: Precast concrete frames (PCFs) with "dry" connections and self-centering capacity have been proposed as a new kind of seismic protective structural system with characteristics of damage controllable mechanism, easy-assemblage and rapid repair speed. The damage mechanism of PCFs are concentrated at the panel zones under earthquake excitations, so as to avoid damage to beam and column components. Through reasonable design for the PCFs, not only the structural and life safeties can be guaranteed, but also the seismic loss and social impact can be minimized. This paper conducts a comparative study between PCFs with "dry" connections and conventional cast-in-situ concrete frame. A generalized beam-column connection analytical model is utilized to predict the seismic behaviour of PCFs with energy dissipation devices, with an emphasis on the opening behaviour at beam-column interfaces, the self-centering capacity provided by prestressed tendons and the hysteresis behaviour provided by energy dissipation devices. Prototype PCFs or cast in situ frame structures are designed to achieve similar deformation capacities in Chinese highly seismic fortification zone. Probabilistic seismic capacity analyses (PSCA) are conducted based on the results of probabilistic pushover analyses and Latin Hypercube Sampling. Incremental dynamic analysis method combined with nonlinear time history analyses are utilized to conduct probabilistic seismic demand analyses (PSDA). Fragility functions of different structural systems are derived based on the convolution of PSCA and PSDA. Finally, the seismic risk is evaluated based on the fragility functions and the developed Chinese seismic code compliant hazard functions. The results indicate that PCFs with energy dissipation devices can have lower seismic risk than conventional cast-in-site frames.